2009
DOI: 10.1096/fj.08-127951
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity during spaceflight directly affects in vitro osteoclastogenesis and bone resorption

Abstract: During space flight, severe losses of bone mass are observed. Both bone formation and resorption are probably involved, but their relative importance remains unclear. The purpose of this research is to understand the role of osteoclasts and their precursors in microgravity-induced bone loss. Three experiments on isolated osteoclasts (OCs) and on their precursors, OSTEO, OCLAST, and PITS, were launched in the FOTON-M3 mission. The OSTEO experiment was conducted for 10 d in microgravity within bioreactors with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 15 publications
5
92
0
Order By: Relevance
“…Recently, in isolated osteoclasts, it was reported that osteoclastic activity increased in those osteoclasts that were cultured in space (Tamma et al, 2009); however, there has been no data relating the interaction between osteoblasts and osteoclasts in space. Although bone mass is reportedly increased by mechanical strain, it has also been reported that mechanical strain on isolated osteoclasts upregulated their bone-resorbing activity (Kurata et al, 2001); therefore, the results obtained from the isolated osteoclast system may differ from that obtained from the in vivo system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in isolated osteoclasts, it was reported that osteoclastic activity increased in those osteoclasts that were cultured in space (Tamma et al, 2009); however, there has been no data relating the interaction between osteoblasts and osteoclasts in space. Although bone mass is reportedly increased by mechanical strain, it has also been reported that mechanical strain on isolated osteoclasts upregulated their bone-resorbing activity (Kurata et al, 2001); therefore, the results obtained from the isolated osteoclast system may differ from that obtained from the in vivo system.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclast differentiation is enhanced in microgravity, and an increase in collagen telopeptides was observed in media samples retrieved from space [88]. Simulated microgravity with high-gradient magnetic fields directly affects cell survival and differentiation of human pre-osteoclast FLG29.1 [89].…”
Section: Differentiationmentioning
confidence: 98%
“…Investigations on the Canadian side included effects of parathyroid hormone (PTH)-related peptide (PTHrP) on osteobasts, the CD200 ligand pathway in osteoblasts and osteoclasts, and the cytoskeleton of bone cells in microgravity. European investigators looked at fibrogenesis of osteoblasts, osteoclast differentiation, and the effects of microgravity on the cross-influence of osteoclasts and osteoblasts (23). The eOSTEO system includes automated hardware specifically designed for bone cell cultures and is currently the system of choice for culturing bone and bone derived cells.…”
Section: Flight Hardware For Bone Biology Studiesmentioning
confidence: 99%